2011
DOI: 10.1002/pssa.201026539
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Ag/TlInSe2/Ag structure

Abstract: In this work, the current-voltage characteristics of Ag/TlInSe 2 / Ag and In/TlInSe 2 /In structures, the incident light intensity and time dependencies of photocurrent as well as the response timeillumination intensity dependence of Ag/TlInSe 2 /Ag structures have been studied. For bias voltages larger than 120.0 and 4.0 V, the current injection was found to be space-charge limited and was assigned to the existing of deep and shallow hole traps being located at 210 and 16 meV for Ag and In-contacted samples, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Similar behavior to ours have also been reported by others. 20,23,[29][30][31][32][33][34] Due to these observations, we concluded that the possible conduction mechanism in this sample is SCLC. 29,35 In the SCLC transport, the current suddenly increases.…”
Section: Current-voltage (I-v) Characteristicsmentioning
confidence: 96%
See 1 more Smart Citation
“…Similar behavior to ours have also been reported by others. 20,23,[29][30][31][32][33][34] Due to these observations, we concluded that the possible conduction mechanism in this sample is SCLC. 29,35 In the SCLC transport, the current suddenly increases.…”
Section: Current-voltage (I-v) Characteristicsmentioning
confidence: 96%
“…This type of high field conduction mechanism has also been found in some other materials. 30,37,38 Temperature Dependence of the Threshold Voltage V th…”
Section: Current-voltage (I-v) Characteristicsmentioning
confidence: 99%